Hemangioblastoma in the lateral ventricle: An extremely rare case report - Pan, Ruihan; Shi, Jianwei; Xu, Yang; Bo, Fuduo; Luo, Zhengxiang; Zhang, Yansong (Frontiers in Oncology, 2022)
Hemangioblastoma (HB) is a benign vascular tumor that accounts for approximately 2% of the intracranial neoplasms. HB of the lateral ventricles is extremely rare. Only a few reports are present in the literature. This article reports a 27-year-old male who arrived at our hospital because of a progressive headache. The brain Magnetic Resonance Imaging (MRI) revealed a solid-cystic mass of 3.5×3.0 cm in size located in the left lateral ventricle. The postoperative CT and MRI showed the successful complete removal of the tumor and a normal ventricle morphology. The differential diagnosis should be considered in case of intraventricular tumors including HB. Angiography should be performed prior to surgery when HB is suspected.